Perilaku Penyiaran Jurnalistik Serta Standar Program Siaran Dalam Bentuk Hidden Camera dan Doorstoping di Era 4.0 - Azizah, Muthia Dini (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
Every action taken by the government must have a strong legal basis so as not to conflict with the legislation. This research was conducted with the aim of knowing how the form of legal arrangements in the implementation of television broadcast content according to laws and regulations and how the responsibility of broadcast organizers in organizing television broadcast content in accordance with laws and regulations. The research method used is library research, which is a series of activities related to library data collection methods. The findings in this article are related to the concepts of fairness, accuracy and impartiality, which are very important in upholding the law and truth. Reporting events of panic, riots and conflicts is crucial to ensuring public safety and addressing their impact, even though there is no specific law governing such matters. Finally, the use of hidden cameras has legal and ethical implications that must be considered in accordance with the Electronic Information and Transaction Law and its amendments to prevent legal violations and protect public privacy.